2016
DOI: 10.1016/j.molmed.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Retinoblastoma: Implications for Cancer, Development, Evolution, and Regenerative Medicine

Abstract: Retinoblastoma is a rare childhood cancer of the developing retina, and studies on this orphan disease have led to fundamental discoveries in cancer biology. Retinoblastoma has also emerged as a model for translational research for pediatric solid tumors, which is particularly important as personalized medicine expands in oncology. Research on retinoblastomas has been combined with the exploration of retinal development and retinal degeneration to advance a new model of cell type–specific disease susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 69 publications
0
29
1
2
Order By: Relevance
“…In RB cells, it has been observed that involvement of the p53 can mediate cell death (33,34). In the present study, the magnitude and kinetics of the changes in p53 caused by CPt alone were quite different from that caused by PTX alone or by the combined actions of PTX and CPt.…”
Section: Discussioncontrasting
confidence: 65%
“…In RB cells, it has been observed that involvement of the p53 can mediate cell death (33,34). In the present study, the magnitude and kinetics of the changes in p53 caused by CPt alone were quite different from that caused by PTX alone or by the combined actions of PTX and CPt.…”
Section: Discussioncontrasting
confidence: 65%
“…Germline mutations in the RB1 gene result in retinoblastomas in >90% of the cases, but these patients also show increased incidence of other cancer types, such as osteosarcomas (Dyer 2016). In order to test whether a defect in BRG1 recruitment was also observed in cancer cells with RB1 mutations, we used the I-PpoI system in a widely used osteosarcoma cell line (SAOS-2) that is known for its inactivation of RB.…”
Section: E2f1mentioning
confidence: 99%
“…RB, caused by autosomal dominant mutations in the RB1 tumor suppressor gene, is a rare cancer of the retina typically found in children with approximately 300 cases in the US and 5–10,000 cases worldwide reported annually [132]. The RB autosomal dominant inheritance pattern suggests that one copy of the RB mutation in each cell is sufficient to increase patient RB risk [132].…”
Section: Figurementioning
confidence: 99%
“…The RB autosomal dominant inheritance pattern suggests that one copy of the RB mutation in each cell is sufficient to increase patient RB risk [132]. Patients with bilateral RB are likely to acquire RB1 germline mutations.…”
Section: Figurementioning
confidence: 99%